Exploring the hydrogeochemical evolution of cold and thermal waters in the Sarein-Nir area, Iran using stable isotopes (δ18O and δD), geothermometry and multivariate statistical approaches. (May 2020) - Barzegar, Rahim; Asghari Moghaddam, Asghar; Tziritis, Evangelos; Adamowski, Jan; Bou Nassar, Jessica; Noori, Mohammad; Aalami, Mohammad Taghi; Kazemian, Naeimeh
Highlights: Statistical analysis showed that the water-rock interaction contributed more to the chemistry of water in the Sarein-Nir area than anthropogenic factors. Based on stable isotope (δ18O and δD) and geothermometry techniques, the majority of thermal water samples were immature. Results demonstrated that springs of the Sarein region showed high temperatures compared to those of the Nir region. Abstract: In recent years, water management in Iran has mostly focused on monitoring, understanding and mitigating issues of water quality. To understand the processes that can affect water quality, this study carried out a geochemical study on cold (5 well water samples and 6 cold springs) and thermal (9 hot springs) waters in the Sarein-Nir area in Iran. A total of 20 water samples were collected in July 2016, and physicochemical variables such as pH, electrical conductivity (EC) and major, minor and trace element concentrations were determined. Using multivariate statistics, the main geochemical processes and possible origin of selected trace elements were investigated. The maturity and mixing processes of the waters were investigated using stable isotope ( δ 18 O and δ D) and geothermometry techniques. It was found that water-rock interaction was the predominant process, and that denitrification and ion exchange processes also took place in the groundwater system of the area. Thermal waters had an elevated EC, whereas cold waters showed elevated pH and NO3 values, indicating the impact of anthropogenic activities on water quality. Alkalinity and temperature were recognized as the most important variables that control the release of trace elements into the groundwater. Most thermal water samples were immature and belonged to peripheral water types, indicating that these samples came in part from deep circulation. Geothermometry of the thermal waters showed that the springs of the Sarein region had high temperatures compared to the springs of the Nir region. Considering that the Sarein spring waters had lower deuterium ratios than spring waters in the Nir region, it was concluded that the recharge elevation of the Sarein springs was higher than that of the Nir springs.